Phenomenological transcendental static analysis on the kinesthetic experience of somersault techniques by advanced gymnasts - Shintake, Y.; Watanabe, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2018)
Attaining refinement and stabilization of motor skills is indispensable to advanced performance in athletics training. When coaches lead gymnasts to a higher performance level, they need to have a flair for fine coordinated movement; in other words, there is a need for kinesthetic information on high-performance movement. However, no previous studies have clarified the characteristics of kinesthetic genesis and structure during the learning process in advanced classes. This paper focuses on the genesis of kinesthetic sensations centering on the somersault techniques of advanced gymnasts. Therefore, phenomenological transcendental static analysis was employed to clarify the kinesthetic sensations related to "swing backward to double sault forward tucked" on uneven bars. This analysis clarified the typical structures of the kinesthetic consciousness of gymnasts who have attained the refined and stabile movement form of "swinging backward to double sault forward tucked" on uneven bars, and the present results may serve as a guide for coaching to attain fine coordination and stabilization.